Analisis Efektivitas Bantuan Benih Terhadap Produksi Padi di Kelurahan Baruga Kecamatan Baruga Kota Kendari - Azizah, Fashihul; Ma'mun, Sitti Rahma; Sufa, Basri (Agrisurya, 2024)
This study aims to analyze the effectiveness of rice seed assistance to determine its effect on production results at three irrigation sites in the rice fields of Amohalo Village, Baruga Village, Baruga District, Kendari City. This research was conducted from June to September 2022 with respondents as many as 30 farmers. The sample in this study was determined using cluster sampling and problem solving in this study using quantitative descriptive analysis and cluster analysis. The results of this study show that seed assistance in three irrigation sites in Baruga Village has been effective but the effectiveness has no real effect on production results, This can be seen from the results of cluster analysis obtained by cluster 1 with dummy characteristics (effectiveness of seed assistance) is not effective but factors and production results are high and cluster 2 has dummy characteristics (effectiveness of seed assistance) is effective but factors and production results are low